Introducing Serine as Cardiovascular Disease Biomarker Candidate via Pathway Analysis: - Zamanian Azodi, Mona; Rezaei Tavirani, Mostafa; Rostami-Nejad, Mohammad; Morravej, Hamideh; Razzaghi, Zahra; Okhovatian, Farshad; Rezaei-Tavirani, Majid (Galen Medical Journal, 2020)
Background: The rate of death due to cardiovascular disease (CVD) is growing. Investigations about CVD that leading to introduce varieties of metabolites is available. The monitoring of these metabolites to find effective ones in the future of clinic applications is the main aim of this study. Materials and Methods: Numbers of 34 metabolites for the CVD are extracted from literature and designated for interaction determinations by MetScape V 3.1.3. The compound-reaction-enzyme-gene network was constructed and the pathways were analyzed. Based on the presence of metabolites in the pathways the critical compounds were determined. Results: Pathway analysis revealed 18 disturbed pathways related to the CVD. glycerophospholipid metabolism pathway including 27 compounds is related to the 9 queried metabolites. L-Serine which was communed between 5 pathways and also was presented in the largest pathway was identified as the critical compound. Conclusion: It can be concluded that L-Serine is a proper biomarker candidate for CVD diagnosis and also patients follow up approaches. [GMJ.2020;9:e1696]